Therapeutic Applications of Curcumin and its Novel Formulations in the Treatment of Bladder Cancer: A Review of Current Evidence - Pourhanifeh, Mohammad H.; Mottaghi, Reza; Razavi, Zahra S.; Shafiee, Alimohammad; Hajighadimi, Sarah; Mirzaei, Hamed (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Bladder cancer, a life-threatening serious disease, is responsible for thousands of cancer-associated deaths worldwide. Similar to other malignancies, standard treatments of bladder cancer, such as Chemoradiotherapy, are not efficient enough in the affected patients. It means that, according to recent reports in the case of life quality as well as the survival time of bladder cancer patients, there is a critical requirement for exploring effective treatments. Recently, numerous investigations have been carried out to search for appropriate complementary treatments or adjuvants for bladder cancer therapy. Curcumin, a phenolic component with a wide spectrum of biological activities, has recently been introduced as a potential anti-cancer agent. It has been shown that this agent exerts its therapeutic effects via targeting a wide range of cellular and molecular pathways involved in bladder cancer. Herein, the current data on curcumin therapy for bladder cancer are summarized.
Keywords: oxidative stress